Association of autonomic symptoms with cerebrospinal fluid biomarkers in Parkinson disease and scans without evidence of dopaminergic deficit - Yu, Zhenwei; Li, Yang (Medicine (Baltimore), 2021)
Dysautonomia is common in patients with Parkinson disease (PD) since disease early phase. Scales for Outcomes in Parkinson's disease - Autonomic (SCOPA-AUT) is a well-designed scale assessing the autonomic dysfunctions of PD patients. Our objectives were to examine the autonomic dysfunction in PD and scan without evidence of dopaminergic deficit (SWEDD) patients and to assess the correlation of autonomic dysfunctions with cerebrospinal fluid (CSF) biomarkers.An analysis of the Parkinson's Progression Markers Initiative (PPMI) data including 414 PD patients, 60 SWEDD patients, and 170 healthy controls (HCs) with baseline CSF biomarker measurements and SCOPA-AUT assessments was presented. Autonomic symptoms including gastrointestinal, urinary, cardiovascular, pupillomotor, thermoregulatory and sexual dysfunctions were assessed by SCOPA-AUT scales. Spearman correlation test was used to examine the correlations between CSF measurements and each section of SCOPA-AUT scales in HCs and subjects with PD or SWEDD.More severe autonomic dysfunctions were observed in patients with SWEDD than those with PD (P < .001). Specifically, patients with PD have lower scores on the urinary scale [4 (0-17) vs 5 (1-18)], pupillomotor scale [0 (0-3) vs 0 (0-3)], thermoregulatory scale [0 (0-4) vs 1.5 (0-10)] and sexual scale [1 (0-6) vs 2 (0-6)] compared with SWEDD patients. Thermoregulatory dysfunction scores were found correlated with CSF α-syn levels in SWEDD group, and gastrointestinal dysfunction scores were correlated with CSF Abeta1-42 in PD group. Additionally, urinary dysfunction scores were correlated with CSF total tau and tau phosphorylated at threonine 181(p-tau181) levels in both HCs and PD patients.